Formulation and Evaluation of Herbal Cough Syrup - Panda, Pratikeswar; Sahu, Arpita (Asian Journal of Pharmaceutical Research and Development, 2023)
The most common problem suffered by individuals everywhere over many centuries is cough. Coughing is the protective mechanism of the body. Coughs are classified further accordingly which are depending upon factors such as signs and symptoms, duration, type, character, etc. Most commonly used, prepared and popular dosage form to cure cough and cold is syrup. The most preferred dosage form to cure cough is herbal syrup, which is used mostly due to its benefits over synthetic syrups. Medicinal plants are used as primary health care agents, mostly in Asian countries. Ingredients showing expectorant antitussive activity are used. Hereby cough and herbal treatments associated with cough are studied briefly. The herbal cough syrup is studied which is liquid dosage form, it is easy to administer than solid dosage form and is more effective and fast acting in order to cure cough. Method of preparation of cough syrups were discussed. The material and quantity used in preparation were listed. Here honey based three batches were performed having concentration such as 35%, 40%, 45% w/v. the quality of final syrup was evaluated for post formulation studies.